Spiritual Companionship: Anam ċara sebagai Seni Praktika yang Hilang di Gereja Kontemporer? - Nindyo Sasongko (Theologia in Loco, 2020)
In this article, I propose the theme of friendship to be an ecclesial practice, a practice adapted from “spiritual direction.” I will approach from different perspective, especially from various Protestant seminaries such as pastoral to clinical pastoral care. Therefore, I propose “spiritual direction” or “spiritual companion.” I will use the philia concept, which is love between two (or more) people who are nonsexual and non-erotic. This love manifests between two friends who are committed to walking together, side by side and looking at one vision and walking together to reach that vision. By borrowing the anam ċara idea, “friend of the soul” from the Celtic-Irish tradition, “spiritual companionship” can become a habitus in Indonesian Christian congregations in order to increase the spirituality of church members.